Hurricanes Irma and Maria and Diabetes incidence in Puerto Rico - Marijulie Martínez-Lozano; Carlamarie Noboa; Gerardo Alvarado-González; Kaumudi J. Joshipura (BMC, 2023)
Abstract Objective To evaluate the impact of Hurricanes Irma/Maria on diabetes incidence in Puerto Rico. Mortality increased substantially after the hurricanes, but morbidity was not assessed. Methods We recruited 364 participants from the San Juan Overweight Adults Longitudinal Study (SOALS) aged 40-65 years who completed a three-year follow-up and were free of diabetes. We conducted additional questionnaires 1.7-2.5 years after hurricanes. Glycosylated hemoglobin (HbA1c), fasting glucose and insulin were assessed at all three visits. We compared diabetes incidence between pre-hurricane visits and between visits spanning the hurricanes using Generalized Estimating Equation (GEE) adjusting for within person repeated measures, age, and body mass index (BMI). Results Diabetes incidence was significantly higher spanning the hurricanes than pre-hurricane (multivariate GEE model: IRR = 2.1; 95% CI: 1.4-3.1). There was a significantly higher increase spanning the hurricanes compared to pre-hurricanes for Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) (median: 0.3 uIU/mL vs. 0.2 uIU/mL). HbA1c levels increased by 0.4% spanning the hurricanes. Conclusion Increases in diabetes incidence, HOMA-IR and HbA1c were higher spanning the hurricanes compared to the pre-hurricanes period. The increase in diabetes incidence remains significant after adjusting for age and BMI.